(untitled) (Olhar de Professor, 2021)
The present reflection takes the pandemic phase together with the contemporary thought as a starting point for the thematic usage of some of the dilemmas that cross the articulating practice of education so commonly used today. For this purpose we evoque the discourse of social inequality described by researchers from different fields of study. With the intent of contrasting the precariousness of the body we will see that this process, already under way, uses the pandemic as the ideal excuse for the emergence of digital technologies in the pedagogical infrastructure with the living presence of students and teachers taken as an obstacle. In this scenario, the pedagogical circle divides itself between the always possible resistance and the inevitability of the precariousness of the body. But there will be body!